2012
DOI: 10.2495/si120231
|View full text |Cite
|
Sign up to set email alerts
|

Satellite based yield and water use targets for horticultural crops grown in SE Australia

Abstract: Satellite-based information was combined with field data to estimate crop water requirement and yield potential in 74 fields of commercial fruit and nut crops grown in the Shepparton and Sunraysia Irrigation Regions of northern Victoria, Australia during the 2011/12 irrigation season. Comparisons of irrigation water supply (grower practice) with satellite-based estimates of crop water requirement showed over-irrigation was commonplace. Comparisons of actual yield with regional-and crop-specific yield targets s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…This study used a single image as a representative of summer season. This is in accordance with a previous study in the irrigation regions of Victoria, Australia, which found the use of single 'midseason' image adequate to assess maximum crop cover because of strong temporal stability in NDVI response [53]. However, for further studies, there is a scope to test temporal aggregates of image-based variables from multiple sources including Landsat-8/9 and Sentinel-2.…”
Section: Discussionsupporting
confidence: 90%
“…This study used a single image as a representative of summer season. This is in accordance with a previous study in the irrigation regions of Victoria, Australia, which found the use of single 'midseason' image adequate to assess maximum crop cover because of strong temporal stability in NDVI response [53]. However, for further studies, there is a scope to test temporal aggregates of image-based variables from multiple sources including Landsat-8/9 and Sentinel-2.…”
Section: Discussionsupporting
confidence: 90%
“…This study used a single image as a representative of the summer season. This is in accordance with a previous study in the irrigation regions of Victoria, Australia, which found the use of a single 'mid-season' image adequate to assess maximum crop cover because of the strong temporal stability in NDVI response [53]. However, for further studies, there is scope to test temporal aggregates of image-based variables from multiple sources including Landsat-8/9 and Sentinel-2.…”
Section: Discussionsupporting
confidence: 89%
“…Our decision to use a single image per irrigation period was in accordance with previous studies. In a study conducted previously on the perennial horticulture crops in the same region, it was found that the use of single 'midseason' image is adequate to assess maximum crop cover because of strong temporal stability in NDVI response (O'Connell 2011, p. 61) [44]. Quoting multiple studies, Velpuri et al (2009, p. 1384) [45] reported that "single date fine-resolution imagery, acquired at critical growth stages, is sufficient to identify irrigation".…”
Section: Discussionmentioning
confidence: 99%